A proteção dos direitos de propriedade intelectual e as estratégias das empresas de sementes e biotecnologia: uma comparação dos casos americano e brasileiro - Yokoyama, Silvia Mine (2014)
The focus of this research is to evaluate whether the adoption of rules protecting new crop varieties and genetically modified plants have impacted the strategies adopted by soybean and corn seed companies in Brazil, when compared to the United States. The results of this double comparison have shown that, in the case of hybrid corn, as it has a natural protection, the stimulus for private investment occurred independently from the existence of the formal protection rules. Such rules were essential to motivate such investment in soybeans, as it was possible to know from the transformation of the seeds industry in Brazil by the end of the 1990s. In addition, although the genetic modification has occurred either in the traits with agronomic characteristics, which consequently promote yield increase, and traits for quality improvement, the demand from the grower has been concentrated in the first type, which economic returns is directly appropriated by them. It was also possible to verify that the complexity of the research and development process and the need for local specific investments justify the high level of global consolidation of the seeds sector with biotechnology and agrochemicals. In those sectors, the possibility of appropriation over the innovation rights was shown to be fundamental to motivate private investment.